The journal O Estandarte like a vehicle of presbyterian education between the years of 1893 and 1903 (Research, Society and Development, 2020)
The aim of this study is to understand the journal “O Estandarte” like an education vehicle from Presbyterian Church from 1893 and 1903. It is important to note that 1893 was the foundation year of the journal and thar 1903, due to diverse divergences, there was a schism in Brazilian Presbyterianism, so that “O Estandarte” started to be directed by the new religious denomination that was born during this division: the Independent Presbyterian Church. The methodology used on this research has qualitative type, in which we select the educational proposals prevalent on this journal. Furthermore, a specialized bibliography helped us to analyze our sources, as well as understanding the national evangelical mentality between the end of nineteenth century and the beginning of twentieth century. We found discussions related to institutions, morality, theology, and politics. In all these cases, the major writers exhorted their readers to adopt the suitable attitudes on their articles. We understand that, in a direct or indirect way, that publications held important educational proposals. We have concluded that this journal became an educator for those who had access to it, during a period of political and social changes in Brazil, when the Presbyterians looked for raise followers among the different sectors of society aiming, this way, entrench their expansion project in the country. We believe that this issue could contribute with the discussions related to Protestant education within the Cultural History perspective.